Species-specific metabolome changes during salinity downshift in sub-Arctic populations of Mytilus edulis and M. trossulus - Sokolova, Inna M.; Kovalev, Anton; Timm, Stefan; Marchenko, Julia; Sukhotin, Alexey (Frontiers in Marine Science, 2024)
The blue mussels Mytilus edulis and Mytilus trossulus are ecologically and economically important species distributed widely across the Northern Hemisphere. Understanding their behavioral and physiological disparities is crucial for assessing their ecological success and aquacultural value. The recent finding of non-native M. trossulus in the White Sea raises concerns regarding its potential competition with native M. edulis and its prospective spread in light of climate change and surface water freshening. We investigated the responses of M. edulis and M. trossulus to salinity variations by examining shell closure thresholds and tissue levels of 35 metabolic intermediates in mussels acclimated to different salinities (25, 16, and 10). The salinity threshold for valve closure was similar in both studied species, but M. trossulus consistently opened at lower salinities (by 0.2–0.7 practical salinity units) compared to M. edulis. Salinity-induced changes in metabolite levels were similar between the two species. Taurine emerged as the dominant osmolyte, comprising over 50% of the total free amino acid pool, with aspartate and glycine contributing 15–30%. Concentrations of taurine, glycine, and total free amino acids declined with decreasing salinity. Taurine to glycine ratios were higher in M. edulis and increased in both species with declining salinity. Acclimation salinity significantly influenced urea cycle intermediates and methionine sulfoxide content, a cellular biomarker of amino acid oxidation. Species-specific differences were observed in purine metabolism, with higher levels of GMP and AMP found in M. edulis. Likewise, aromatic amino acids and histidine levels were higher in M. edulis compared to M. trossulus. However, no evidence suggests superior adaptation of M. trossulus metabolism to hypoosmotic stress compared to M. edulis. Further research is necessary to elucidate the functional implications of subtle metabolic differences between these Mytilus congeners and their ecological consequences in changing marine environments.